Productivity shocks, international trade and import prices: Evidence from agriculture - Shon Ferguson; Johan Gars (Research Institute of Industrial Economics (IFN), 2016)
The purpose of this study is to measure the sensitivity of trade volumes and unit values to agricultural productivity shocks at home and abroad. We find that the unit values of trade ows vary systematically with production shocks using both aggregate data on a large sample of countries and detailed firm-level imports to Sweden. We find that import prices increase (and import volumes fall) when importer production increases. This result is likely driven by a change in the quality composition of imports or by economies of scale in international trade. This beneficial terms-of-trade effect that we find may thus be an important coping mechanism for food net-importing countries that experience negative production shocks. Our results also suggest that trade volumes are relatively insensitive to changes in production. The results suggest that trade frictions, product differentiation and storage limit the role of international trade as way of coping with production volatility.
Keywords: F14; F18; Q11; Q17; Q18; 330; Climate shocks; pass-through; quality sorting; agricultural trade